1995
DOI: 10.1111/j.1365-2141.1995.tb08916.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of erythropoiesis in haemodialysis patients demonstrates gradual expansion of erythroblasts during constant reatment with recombinant human erythropoietin

Abstract: Recombinant human erythropoietin (rHuEpo) has been shown to be effective in correcting the anaemia of chronic renal failure. It has been reported that reticulocytes as well as erythroid progenitors increase within 1-2 weeks, with no further elevation beyond this time interval. However, the erythroblast pool is quantitatively the most important compartment of erythropoiesis, and the rate, extent and duration of the expansion of erythropoietic activity in response to rHuEpo is not known. Treatment with rHuEpo wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 10 publications
1
8
0
4
Order By: Relevance
“…Serum soluble transferrin receptor, a truncated monomer of cell surface-expressed transferrin receptor, is primarily released from erythroblasts, and its serum level reflects the erythropoietic activity of BM and spleen. 26,27 We also observed multilobed polymorphonuclear neutrophils in the PCFT Ϫ/Ϫ blood smears and giant metamyelocytes in the PCFT Ϫ/Ϫ BM, consistent with abnormal myelopoiesis often observed in patients with folate deficiencyinduced anemia. Internal bleeding in the cerebral vasculature and bloody stools were also noted in PCFT Ϫ/Ϫ mice, which too is often associated with folate deficiency-induced anemia.…”
Section: Discussionmentioning
confidence: 64%
“…Serum soluble transferrin receptor, a truncated monomer of cell surface-expressed transferrin receptor, is primarily released from erythroblasts, and its serum level reflects the erythropoietic activity of BM and spleen. 26,27 We also observed multilobed polymorphonuclear neutrophils in the PCFT Ϫ/Ϫ blood smears and giant metamyelocytes in the PCFT Ϫ/Ϫ BM, consistent with abnormal myelopoiesis often observed in patients with folate deficiencyinduced anemia. Internal bleeding in the cerebral vasculature and bloody stools were also noted in PCFT Ϫ/Ϫ mice, which too is often associated with folate deficiency-induced anemia.…”
Section: Discussionmentioning
confidence: 64%
“…Soluble TfR is of particular interest in assessing response to recombinant human erythropoietin (rHuEpo) in patients with chronic renal failure [32,33], aplastic anemia [34], pure red cell aplasia [35], thalassemia intermedia [36], cancer [37 -39], myelodysplastic syndrome (MDS) [37,40], rheumatoid arthritis [41], genetic hemochromatosis [42] or in intensive care [43], as well as in normal subjects [44], autologous blood donors [45] and premature infants [46] or after stem cell transplantation [47,48]. Similarly, sTfR levels can be used to monitor how erythropoiesis subside after cessation of rHuEpo therapy [49].…”
Section: Main Characteristicsmentioning
confidence: 99%
“…In response to rHuEpo, the erythroblast compartment is very slow to respond, expanding over a period of 6 weeks before reaching a steady state during which the Hb continue to rise [32]. The dose of rHuEpo needed to achieve response is highly variable because of such interfering factors as functional iron deficiency or inflammation.…”
Section: Main Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence have indicated that the direct relationship to the number of erythroid precursors makes soluble TfR assay the method of choice for evaluation of erythroid marrow activity in clinical settings. Indeed, serial measurements of TfR are useful for the quantitative assessment of erythropoietic activity in hemodialysis (HD) patients who are treated with recombinant human erythropoietin (rHuEPO) (2,3) and for monitoring the hemoglobin response to rHuEPO therapy (4). The body iron status is the second major determinant of soluble TfR, and circulating receptor levels rise in the iron-depleted status as a result of the posttranscriptional modification of TfR mRNA expression in the erythroid precursors (5).…”
mentioning
confidence: 99%